Blunt Thoracoabdominal Trauma with Multiple Injuries in a Motorcycle Accident: A Complex Case Report in the Emergency Room - Rocha, Ana Paula de Carvalho Miranda Rosati; Rosati, Luis Fernando; Abbade, Marcos Alvin; Rocha, Ana Luiza de Carvalho Miranda Rosati; Lima, Vinícius Alves Carneiro (Brazilian Journal of Case Reports, 2024)
This report describes the case of a 53-year-old male involved in a motorcycle collision in Itaboraí, RJ, in August 2024. The patient was admitted to the emergency room in hypovolemic shock and received fluid resuscitation with 1000 ml of Ringer’s lactate, resulting in hemodynamic improvement. Initial tests showed a normal hematocrit of 38% and hemoglobin of 12 mg/dl; however, a second test revealed a hematocrit drop to 32%. Contrast-enhanced computed tomography (CT) revealed solid organ injuries, including a grade IV renal injury and a grade III splenic injury, as well as rib fractures and a small left-sided hemothorax. Due to the patient’s hemodynamic stability and the absence of peritoneal irritation signs, non-operative management (NOM) was chosen, with admission to the intensive care unit (ICU) for close monitoring. This report discusses the importance of contrast-enhanced CT for accurate lesion diagnosis and ICU monitoring in NOM cases for complex injuries, highlighting the critical role of the trauma surgeon in patient management.